Hofmeister Effect Assisted Dual‐Dynamic‐Bond Cross‐Linked Organohydrogels with Enhanced Ionic Conductivity and Balanced Mechanical Properties for Flexible Sensors. (15th January 2023) - Guo, Ruyue; Bao, Yan; Zheng, Xi; Zhang, Wenbo; Liu, Chao; Chen, Jie; Xu, Jiachen; Wang, Luxuan; Ma, Jianzhong
Abstract: For soft electronic applications, the simultaneous incorporation of conductivity and mechanical robustness remains a grand constraint, not to mention being able to operate at wide temperatures ranges. Herein, a novel conductive platform is proposed by designing skin‐inspired ionic organohydrogels based on Hofmeister effect and glycerol/water system, which simultaneously realize balanced conductivity, mechanical strength, and versatile properties. The comprehensive performances are broadly and simultaneously altered via tuning the aggregation states of polymer chains by kosmotropes or chaotropes. With various ions, the conductivity and mechanical strength are continuously in situ modulated over a large window: conductivity from 0.08 to 4.8 S m −1, strength from 0.01 to 17.30 MPa, toughness from 5.4 to 9236.9 kJ m −3, and modulus from 5.1 to 2258.9 kPa. The ion transport process is inseparable from the changes of water content and pore structures caused by cross‐linking density. Meanwhile, the mechanical properties greatly depend on the densification or loosing of polymer chains and crystalline domains. Furthermore, oil/water system exhibits low temperature tolerance at ≈−65–15 °C and long‐term stability. Finally, the champion organohydrogels are applied as wearable electronic sensors and artificial skins. The mechanism proposed in this work advances the understanding of the ions contribution to organohydrogels for electronic applications. Abstract : A solvent replacement strategy based on Hofmeister effect and oil‐water system is proposed for simultaneously realizing balanced conductivity, mechanical strength, and versatile properties of skin‐inspired ionic organohydrogels. The conductivity and mechanical properties are broadly and simultaneously altered by kosmotropes or chaotropes, and the mechanisms are studied in detail. Furthermore, oil‐water system endows organohydrogels with operation at wide temperatures ranges.